2014
DOI: 10.1097/spv.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatment of Urinary Incontinence

Abstract: We present an overview of the current pharmacological treatment of urinary incontinence (UI) in women, according to the latest evidence available. After a brief description of the lower urinary tract receptors and mediators (detrusor, bladder neck, and urethra), the potential sites of pharmacological manipulation in the treatment of UI are discussed. Each class of drug used to treat UI has been evaluated, taking into account published rate of effectiveness, different doses, and way of administration. The preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Usage could result in thirst, uncontrolled urination, urination constipation and other adverse reactions, so, single use of such drugs could increase incidence of urinary retention. Currently, obstruction relief drugs were given or operation was performed to improve symptoms, two researches TSUJIMURA [10] and KAPLAN [11] showed that the Hu/Zhang/Guan combined use of α1-adrenergic receptor blockers and M receptor blocker was more reliable in clinical safety and could reduce the incidence of urinary retention [12][13][14], while single use of α1-adrenergic receptor blockers had better curative effects and less adverse reactions than combined use in treating OAB, so, anticholinergic agents or combined use of other drugs were the first choice in clinic. TURP was common in treating OAB in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Usage could result in thirst, uncontrolled urination, urination constipation and other adverse reactions, so, single use of such drugs could increase incidence of urinary retention. Currently, obstruction relief drugs were given or operation was performed to improve symptoms, two researches TSUJIMURA [10] and KAPLAN [11] showed that the Hu/Zhang/Guan combined use of α1-adrenergic receptor blockers and M receptor blocker was more reliable in clinical safety and could reduce the incidence of urinary retention [12][13][14], while single use of α1-adrenergic receptor blockers had better curative effects and less adverse reactions than combined use in treating OAB, so, anticholinergic agents or combined use of other drugs were the first choice in clinic. TURP was common in treating OAB in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that 5HT- 2C activation of the receptor could actively enhance urethral closure during sneezing. In addition to duloxetine, imipramine, which is a norepinephrine and serotonin reuptake inhibitor, is thought to improve urethral smooth muscle contraction for the treatment of SUI or mixed urinary incontinence ( Cipullo et al, 2014 ). Moreover, venlafaxine (0.1–10 mg/kg) and S-norfluoxetine (0.01–10 mg/kg) have also been shown to increase bladder volume, but they have not shown a clear therapeutic effect on SUI.…”
Section: Neurogenic Factorsmentioning
confidence: 99%
“…Anticholinergic medications competitively inhibit acetylcholine at postganglionic muscarinic receptors, resulting in smooth muscle relaxation in the bladder (and other organs) [48]. Common side effects include dry eyes, dry mouth, constipation, urinary retention, dizziness, and blurry vision [22,31,49]. Long-term cumulative anticholinergic use is correlated with an increased risk of all-cause dementia and Alzheimer's disease, and prescribers should be comfortable counseling about these side effects [22,31].…”
Section: Oral Medicationsmentioning
confidence: 99%